2018
DOI: 10.1111/acer.13886
|View full text |Cite
|
Sign up to set email alerts
|

Daily Drinking Is Associated with Increased Mortality

Abstract: Background: There is evidence that low-level alcohol use, drinking 1–2 drinks on occasion, is protective for cardiovascular disease, but increases the risk of cancer. Synthesizing the overall impact of low-level alcohol use on health is therefore complex. The objective of this paper is to examine the association between frequency of low-level drinking and mortality. Methods: Two datasets with self-reported alcohol use and mortality follow-up were analyzed: N=340,668 individuals from the National Health Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 46 publications
0
30
0
1
Order By: Relevance
“…Participants who had used any kind of these substances more than once in the preceding month were classified as having specific substance use. A massive epidemiological study indicated that drinking more than 3 to 4 times weekly significantly increased cardiovascular and cancer mortality in men [24]. To identify those with unhealthy alcohol use, we set the cutoff point at "drinking more than twice per week", including the categories of "twice to thrice per week" and "four times per week or above".…”
Section: Substance Usementioning
confidence: 99%
“…Participants who had used any kind of these substances more than once in the preceding month were classified as having specific substance use. A massive epidemiological study indicated that drinking more than 3 to 4 times weekly significantly increased cardiovascular and cancer mortality in men [24]. To identify those with unhealthy alcohol use, we set the cutoff point at "drinking more than twice per week", including the categories of "twice to thrice per week" and "four times per week or above".…”
Section: Substance Usementioning
confidence: 99%
“…Alcohol use is a leading risk factor for global disease burden, and recent findings indicate that even light-to-moderate drinking is detrimental to all-cause mortality [1,2]. Additionally, approximately 14% of US adults annually, and nearly 30% for lifetime, engage in harmful drinking consistent with alcohol use disorder [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports indicate the beneficial effect of a low intake of alcoholic beverages on the reduction of CDV risk [16,17,18]. However, the definition of light, moderate, or heavy alcohol consumption differed substantially among studies.…”
Section: Introductionmentioning
confidence: 99%